Misinterpretation of speaker intent in a multilingual workforce - Rita Ribbens (Communicare)
This article deals with communication problems in intercultural communication in the workplace. Findings from this study have practical implications for developers of both intercultural and language courses. The research established that a beckoning gesture commonly used by white people is regarded as offensive by most blacks. At the same time many whites are unaware of non-verbal politeness markers signalled by means of kinetics. What whites interpret as "blunt" requests (often regarded as demands) can be ascribed to different norms of communication in African languages. These findings have implications for successful intercultural communication in an industrial society. Awareness of differences in verbal and non-verbal behaviour (termed mutual ignorance by Reagan) needs to be included in training for all members of the multicultural workforce.